Six-year mortality associated with living alone and loneliness in Swedish men and women born in 1930 - Masuma Novak; Margda Waern; Lena Johansson; Anna Zettergren; Lina Ryden; Hanna Wetterberg; Therese Rydberg Sterner; Madeleine Mellqvist Fässberg; Pia Gudmundsson; Ingmar Skoog (BMC Geriatrics, 2023)
Abstract Background This study examined how living alone and loneliness associate with all-cause mortality in older men and women. Methods Baseline data from the Gothenburg H70 Birth Cohort Studies, including 70-year-olds interviewed in 2000 and 75-year-olds (new recruits) interviewed in 2005 were used for analyses (N = 778, 353 men, 425 women). Six-year mortality was based on national register data. Results At baseline, 36.6% lived alone and 31.9% reported feelings of loneliness. A total of 72 (9.3%) participants died during the 6-year follow-up period. Cumulative mortality rates per 1000 person-years were 23.9 for men and 9.6 for women. Mortality was increased more than twofold among men who lived alone compared to men living with someone (HR 2.40, 95% CI 1.34–4.30). Elevated risk remained after multivariable adjustment including loneliness and depression (HR 2.56, 95% CI 1.27–5.16). Stratification revealed that mortality risk in the group of men who lived alone and felt lonely was twice that of their peers who lived with someone and did not experience loneliness (HR 2.52, 95% CI 1.26–5.05). In women, a more than fourfold increased risk of mortality was observed in those who experienced loneliness despite living with others (HR 4.52, 95% CI 1.43–14.23). Conclusions Living alone was an independent risk factor for death in men but not in women. Mortality was doubled in men who lived alone and felt lonely. In contrast, mortality was particularly elevated in women who felt lonely despite living with others. In the multivariable adjusted models these associations were attenuated and were no longer significant after adjusting for mainly depression in men and physical inactivity in women. Gender needs to be taken into account when considering the health consequences of living situation and loneliness.